Pengaruh Kebiasaan Bermain Game Online terhadap Prestasi Belajar Siswa SD - Ika Kurniawati; Heru Utomo (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Abstract: This research is a library research that aims to determine the effect of online games on the learning achievement of elementary school students. The type of research used is library research or literature review. Analysis of the data used in this study is simplification of data, presentation of data and drawing conclusions on the data used. Data collection techniques were carried out by reading and recording important information contained in various journals related to the research being conducted. The results of the study indicate that a child who is addicted to playing online games will affect his learning achievement. The conclusion from the results of this study is that there is a relationship between the influence of the habit of playing online games with the learning achievement of elementary school students.